The diagnostic value of IRF4 and FGF23 in gingival crevicular fluid and serum for dentin hypersensitivity was compared - Song, Can; Jia, Yubao; Liu, Yaxuan; Zhang, Yujie; Yu, Jing; Xian, Mengmeng (Journal of Medical Biochemistry, 2025)
Objective: The aim of this study is to investigate the diagnostic value of interferon regulatory factor 4 (IRF4) and fibroblast growth factor 23 (FGF23) in gingival crevular fluid (GCF) and serum for dentin hypersensitivity (DH), and to analyze the relationship between IRF4, FGF23 and inflammatory factors and T lymphocyte subsets.Methods: 24 DH patients receiving orthodontic treatment at our institution between 2022 and early 2025 were enrolled as the study cohort, along with 124 healthy controls matched for age and sex. GCF and serum samples were obtained 48 hours post-desensitization therapy to quantify IRF4 and FGF23 levels (via enzyme-linked immunosorbent assay), along with serum inflammatory markers (interleukin [IL]-1β, IL-6, high-sensitivity C-reactive protein [hs-CRP]) and T-cell subpopulations (CD3+, CD4+, CD8+). Statistical analyses included Pearson's correlation to examine relationships between IRF4/FGF23 and clinical parameters, with receiver operating characteristic (ROC) curve analysis determining diagnostic accuracy.Results: The study revealed that GCF and serum levels of IRF4 and FGF23 were markedly elevated in DH patients compared to healthy controls (P